(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Microfinance organizations and their theoretical foundations are studied. The main directions of development of microfinance organizations. The economic and legal foundations of microfinance organizations and the current state of microfinance organizations are analyzed. Innovative financial products. Development of fintech innovations. A lack of alignment with the organization’s overall strategy has often been cited as a possible reason for financial services failure. The concept of Microfinance-corporate strategy alignment, however, is neither well-defined nor understood. This study endeavors to contribute a better understanding of this concept and to provide managers with a model to measure this alignment. In most organizations that adopt opportunities along with Fintech, a strategic financial services and micro finance plan is made the four key components: (1) goal formation, (2) strategy development, (3) resource deployment and (4) outcome metrics. For Micro financial organizations to gain recognition among financial managers, it must guarantee its alignment with the organization’s corporate strategy. To assess the extent of this alignment, organizations need to create a shared vision among its members, good governance, appropriate risks and rewards.